Implementasi Tradisi Syawalan pada Pembelajaran Matematika Berbasis Etnomatematika - Syifa, Nailatusy; Salafudin (Circle: Jurnal Pendidikan Matematika, 2021)
The research issues show that mathematics lessons are often monotonous and theoretical as well as the similarity of practice questions for students from year to year. And the societies do not realize that this tradition has a mathematical concept in its construction. This study aims to analyze the implementation of the Syawalan tradition and its relation to the learning material and its application in making math problems. This research is descriptive qualitative. Data were obtained from the results of observations, interviews, and documentation. Data collected are in the form of images or descriptions of data acquisition results. The results of this research show that syawalan tradition of “giant lopis” and “hot air balloon” has several mathematical concepts in the same form as space and its construction also uses mathematics such as measuring and metering which is also related to mathematics subject matter. Mathematics subject matter related to the giant lopis tradition, namely comparisons, Pythagorean theorem, flat shapes and curved side spaces. Whereas in the hot air balloon tradition, there are quadratic function equations, comparisons, Pythagorean theorem and flat shapes. Therefore, these can be implemented in students’ practice questions. The results of this study can be used as a source of learning mathematics with existing concepts in the tradition of giant lopis and hot air balloons in order to compose innovative and contextual mathematics learning. It will also make it easier for the makers for using math cocepts in lopis and balloons construction.